Down-Regulation of PpBGAL10 and PpBGAL16 Delays Fruit Softening in Peach by Reducing Polygalacturonase and Pectin Methylesterase Activity - Liu, Hangkong; Qian, Ming; Song, Chunhui; Li, Jinjin; Zhao, Caiping; Li, Guofang; Wang, Anzhu; Han, Mingyu (Frontiers in Plant Science, 2018)
β-galactosidases are cell wall hydrolases that play an important role in fruit softening. However, PpBGALs mechanism impacting on ethylene-dependent peach fruit softening was still unclear. In this study, we found that PpBGAL4, -6, -8, -10, -16 and -17 may be required for ethylene-dependent peach softening and PpBGAL10, -16 may make a main contribution to it among 17 PpBGALs. Utilization of virus-induced gene silencing (VIGS) showed that fruits were firmer than those of the control at 4 and 6 days after harvest (DAH) when PpBGAL10 and PpBGAL16 expression was down-regulated. Suppression of PpBGAL10 and PpBGAL16 expression also reduced PpPG21 and PpPME3 transcription, and polygalacturonase (PG) and pectinmethylesterases (PME) activity. Overall, total cell wall material and protopectin slowly declined, water-soluble pectin slowly increased, and cellulose and hemicellulose was altered significantly at 4 DAH, relative to control fruit. In addition, PpACO1 expression and ethylene production were also suppressed at 4 DAH because of inhibiting PpBGAL10 and PpBGAL16 expression. These results suggested that down-regulation of PpBGAL10 and PpBGAL16 expression delays peach fruit softening by decreasing PG and PME activity, which inhibits cell wall degradation and ethylene production.